PENGARUH ORGANIZATIONAL LEARNING TERHADAP COMPETITIVE ADVANTAGE MELALUI ACCOUNTING INFORMATION SYSTEM PADA PERUSAHAAN NON MANUFAKTUR TERBUKA - Pranata, Andrew (Business Accounting Review, 2015)
The purpose of this study was to know whether there was an influence of organizational learning to competitive advantage through the accounting information system. The selected population in this study was open non-manufacturing companiesÂ  Surabaya, which is composed of property, telecommunications, banks, and retail. Sample of this research was the employee who has a position as a manager. The total sample of 60 respondents drawn 2 managers from each company manager. This study used path analysis technical model with PLS. The results from this study showed that organizational learning had significant and positive impact on the competitive advantage of companies and also learning through the accounting information system that could give affect to the company in achieving competitive advantage.